2019
DOI: 10.1039/c9se00108e
|View full text |Cite
|
Sign up to set email alerts
|

Study on catalyst selection for electrochemical valorization of glycerol

Abstract: Navigating glycerol electrochemical oxidation roadmap and catalyst selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 165 publications
2
130
0
Order By: Relevance
“…While many products used to be obtained at metallic electrocatalysts, 35,[40][41][42] only two main products have been obtained in this study, for instance formic and glycolic acids at the selectivity of 66 and 32%, respectively (oxalic acid is 1.8%, glyceric acid is 0.7 % and tartronic acid 0.1%). The determined exchanged number of electrons that are transferred is about 6, which is in agreement with the production of the carboxylate forms of those products in alkaline media so that the faradaic yield is about 86%.…”
Section: The Experimental Procedures Are Reported In the Electronic Smentioning
confidence: 95%
“…While many products used to be obtained at metallic electrocatalysts, 35,[40][41][42] only two main products have been obtained in this study, for instance formic and glycolic acids at the selectivity of 66 and 32%, respectively (oxalic acid is 1.8%, glyceric acid is 0.7 % and tartronic acid 0.1%). The determined exchanged number of electrons that are transferred is about 6, which is in agreement with the production of the carboxylate forms of those products in alkaline media so that the faradaic yield is about 86%.…”
Section: The Experimental Procedures Are Reported In the Electronic Smentioning
confidence: 95%
“…It is worth mentioning that the reported precious metal-free materials to electro-catalyze the oxidation of glycerol need a potential range of 1.4-1.9 V vs RHE in order to get high current densities, as recently reviewed by the group of Baranova. 27 Given the higher potential, the idea of using an organic compound to lower the potential of the anode apparently violates the initial need of reducing the proportion of energy consumed by the anode, of the order of 90% in conventional water electrolyzer. 18,23 Those facts explain why the presence of the three metals Au, Pt or Pd, which are the only species giving good activity in low potentials, is practically unavoidable for the development of reliable anodes for the organics oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, it was observed a low conversion combined with a high selectivity or high conversion together with low selectivity. [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Recently, Liu et al 40 reported the photoelectrochemical oxidation of 1,3-DHA directly from glycerol using nanoporous BiVO 4 , with high conversion and selectivity of 51%. However, side products such as glyceric acid, formic acid, glycolic acid, CO 2 , CO and H 2 O 2 and O 2 were observed.…”
Section: Expeditious Syntheses To Pharmochemicals 13-dihydroxyacetonmentioning
confidence: 99%